Dai manoscritti alla "princeps": indizi sui tempi e le modalità di allestimento del "libro" per Cassandra Marchese (= "Sonetti et canzoni" 33-98) (Quaderni di Gargnano, 2020)
By means of a parallel study of the manuscript tradition and the final result of the first edition, printed in 1530, new interpretative hypotheses are set forth leading to a sounder identification of the “book” of rhymes offered to Cassandra Marchese (Sonetti et Canzoni 33-98), which – despite Dionisotti’s claims – must have been put together by Sannazaro sometime between 1526 and the year of his death. Attraverso lo studio in parallelo della tradizione manoscritta e l'esito finale della princeps del 1530 si propongono nuove ipotesi interpretative per una più cogente individuazione del "libro" di rime offerto a Cassandra Marchese (Sonetti et Canzoni 33-98), che, diversamente da quanto sostenuto da Dionisotti, deve ritenersi allestito da Sannazaro tra il 1526 e l'anno della morte.
Keywords: Sannazaro; Sonetti et canzoni; tradizione manoscritta; princeps; Cassandra Marchese